Analisis Implementasi Quick Respon Indoneian Standard (QRIS) Sebagai Alat Transaksi Pembayaran Dalam Upaya Peningkatan Pendapatan Pelaku Usaha Mikro Kecil (UMK) Di Tanjung Jabung Timur Dalam Perspektif Maslahah - Rosnaida Rosnaida; M. Iqbal Bafadhal; Ridhwan . (JOURNAL OF SHARIA ECONOMICS, 2025)
Research on "Analysis of the Implementation of Quick Response Indonesian Standard (QRIS) as a Payment Transaction Tool in Efforts to Increase the Income of Micro, Small Enterprises (UMK) in East Tanjung Jaung in a Maslahah Perspective" This analysis was carried out to find out how QRIS is implemented in an effort to increase income in MSEs. is in East Tanjung Jabung. This research is a type of field research using qualitative data from various literature. The research object is business actors in East Tanjung Jabung by examining the application of qris as a means of payment transactions in an effort to increase the opinions of the actors. This research used 10 informants from micro and small business actors in East Tanjung Jabung. Meanwhile, the methods used to collect data are observation, interviews, and no documentation. The results show that the use of QRIS as a payment transaction tool provides convenience, speed and security for each transaction, as well as helping to increase income in the business, according to the maslahah perspective where the implementation of QRIS as a payment transaction tool provides convenience, speed and security for its users, which can seen from the perspective of maslahah which can be interpreted as prioritizing other people's needs, prioritizing other people's affairs and providing benefits to other people.